Highly Sensitive Terahertz Gas Sensor Based on Surface Plasmon Resonance With Graphene - Yuanjiang Xiang; Jiaqi Zhu; Leiming Wu; Qi You; Banxian Ruan; Xiaoyu Dai (IEEE Photonics Journal, 2018)
One of the most important applications of THz frequencies is biomedical sensing. However, in a THz range, surface plasmon waves on flat metals are not confined and therefore cannot be used for subwavelength sensing. But, it has been shown that graphene can support surface waves at THz frequencies, which has similar properties as plasmonic waves in an optical range. In this paper, a highly sensitive gas sensor in the terahertz frequencies by exciting surface plasmon resonance (SPR) of graphene is proposed. The results show that the proposed SPR gas sensor has high stability and high sensitivity (S), and the highest Smax (∼147°/RIU) has been obtained by optimizing the Fermi energy, the thickness of the dielectric layer, and the incident light frequency. Moreover, the S of the proposed THz sensor for different refractive index (RI) of gas sensing medium (n1) is also discussed.